2019
DOI: 10.1038/s41467-019-11500-6
|View full text |Cite|
|
Sign up to set email alerts
|

CD146-HIF-1α hypoxic reprogramming drives vascular remodeling and pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a vascular remodeling disease of cardiopulmonary units. No cure is currently available due to an incomplete understanding of vascular remodeling. Here we identify CD146-hypoxia-inducible transcription factor 1 alpha (HIF-1α) cross-regulation as a key determinant in vascular remodeling and PAH pathogenesis. CD146 is markedly upregulated in pulmonary artery smooth muscle cells (PASMCs/SMCs) and in proportion to disease severity. CD146 expression and HIF-1α transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 61 publications
(82 reference statements)
2
71
0
2
Order By: Relevance
“…CD146 is a molecule expressed in pulmonary artery smooth muscle cells, and its expression level indicates the severity of the disease. Recently, Luo et al demonstrated that the CD146–HIF1-α axis is responsible for vascular remodeling and PH, suggesting that the inhibition of this axis could be an innovative and effective therapeutic strategy against PH [ 99 ]. Even HIF2-α is able to affect the pathogenesis of PH.…”
Section: Dual Role Of Hypoxia In Acute and Chronic Disease Conditimentioning
confidence: 99%
“…CD146 is a molecule expressed in pulmonary artery smooth muscle cells, and its expression level indicates the severity of the disease. Recently, Luo et al demonstrated that the CD146–HIF1-α axis is responsible for vascular remodeling and PH, suggesting that the inhibition of this axis could be an innovative and effective therapeutic strategy against PH [ 99 ]. Even HIF2-α is able to affect the pathogenesis of PH.…”
Section: Dual Role Of Hypoxia In Acute and Chronic Disease Conditimentioning
confidence: 99%
“…HIF-1, composed of the HIF-1α functional subunit and the HIF-1β constitutional subunit ( Luo et al, 2019 ), plays an important role in sensing and adapting to changes in oxygen concentration and is associated with cellular energy metabolism and apoptosis ( Soni and Padwad, 2017 ). HIF-1 is an important target for diseases related to oxygen deprivation ( Albadari et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data that support this study are available from the corresponding author upon reasonable request. Extended Material and Methods section are available in the Supplementary material online [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Methodsmentioning
confidence: 99%